The frequency of DISC1 Leu607Phe gene polymorphism in schizophrenia patients at Dr. Soetomo General Hospital Surabaya - gwenny Ichsan Prabowo; Margarita Maria Maramis; Erikavitri Yulianti; Afrina Zulaikah; Zain Budi Syulthoni; Hendy Muagiri Margono; Retno Handajani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Schizophrenia is a common health problem in the world, including in Indonesia.Polymorphism of gene disrupted in schizophrenia 1 (DISC1) Leu607Phe is allegedly relatedto the predisposition to schizophrenia. However, studies on the relationship betweenpolymorphism of DISC1 Leu607Phe and schizophrenia in various etnics provided differentresults. The purpose of this study was to determine the frequency of DISC1 Leu607Phegenepolymorphism and its association with treatment response in patients with schizophreniaat Department of Psychiatry, Dr. Soetomo General Hospital Surabaya. In this study, thenumber of male patients with schizophrenia was more than that of the female patients.The mean age of male patients with schizophenia was lower than that of the femalepatients. Schizophrenia patients were primarily came from Javanese ethnic with positiveand negative symptom score (PANSS) lower in male patients than that in the femalepatients. In conclusion, no DISC1 gene polymorphism at codon 607 is observed inschizophrenia patients at Dr. Soetomo General Hospital Surabaya, but the G nucleotidevariation at the number 196.339 in intron regions is found instead.